2022
DOI: 10.1186/s13007-022-00847-5
|View full text |Cite
|
Sign up to set email alerts
|

A foliar pigment-based bioassay for interrogating chloroplast signalling revealed that carotenoid isomerisation regulates chlorophyll abundance

Abstract: Background Some plastid-derived metabolites can control nuclear gene expression, chloroplast biogenesis, and chlorophyll biosynthesis. For example, norflurazon (NFZ) induced inhibition of carotenoid biosynthesis in leaves elicits a protoporphyrin IX (Mg-ProtoIX) retrograde signal that controls chlorophyll biosynthesis and chloroplast development. Carotenoid cleavage products, known as apocarotenoids, also regulate plastid development. The key steps in carotenoid biosynthesis or catabolism that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…NFZ treatment of seedlings blocks downstream carotenoid biosynthesis and elicits a retrograde signal that suppresses PhANG expression to thereby impair plastid biogenesis (Wu and Bock, 2021). ccr2 also blocks carotenoid accumulation in etiolated tissues, yet the lack of any PLB formation in ccr2 etioplasts and a unique transcriptomic profile indicated that ccr2 could trigger both independent and overlapping signalling pathways (Cazzonelli et al, 2020;Dhami et al, 2022). While εLCY has not been considered a traditional PhANG like LHCB1, our evidence reveals that both these genes are repressed in NFZ-treated etiolated seedlings.…”
Section: Changes In Cyclic Carotenoids Trigger Metabolic Feedback Reg...mentioning
confidence: 63%
See 2 more Smart Citations
“…NFZ treatment of seedlings blocks downstream carotenoid biosynthesis and elicits a retrograde signal that suppresses PhANG expression to thereby impair plastid biogenesis (Wu and Bock, 2021). ccr2 also blocks carotenoid accumulation in etiolated tissues, yet the lack of any PLB formation in ccr2 etioplasts and a unique transcriptomic profile indicated that ccr2 could trigger both independent and overlapping signalling pathways (Cazzonelli et al, 2020;Dhami et al, 2022). While εLCY has not been considered a traditional PhANG like LHCB1, our evidence reveals that both these genes are repressed in NFZ-treated etiolated seedlings.…”
Section: Changes In Cyclic Carotenoids Trigger Metabolic Feedback Reg...mentioning
confidence: 63%
“…The loss-of-function in crtiso (ccr2) triggers cis-carotene accumulation and suppresses εLCY expression in etiolated seedlings (Cuttriss et al, 2007). We recently reported a cis-ACS regulated plastid biogenesis, HY5, PIF3, and PhANG expression in etiolated and de-etiolated seedlings, as well as young emerging leaves of ccr2 that accumulate linear cis-carotenes (Cazzonelli et al, 2020;Dhami et al, 2022). We questioned if metabolic feedback regulation of εLCY expression was also linked to linear cis-carotene accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After prolycopene biosynthesis and prior to the branch of the epsilon/beta-branch in the pathway, CRTISO regulates isomerisation together with light forming a unidirectional photoswitch that rate-limits cis-carotene levels (Alagoz et al, 2018;Nayak et al, 2022). CRTISO appears to be the key rate-limiting step inducing threshold levels of acyclic linear cis-carotenes that impair signalling of plastid biogenesis (Dhami et al, 2022). During skotomorphogenesis, the etioplasts of seedling tissues develop prolamellar bodies (PLB), the characteristic paracrystalline membrane structure that defines etioplasts and accelerates photomorphogenesis upon illumination (Park et al, 2002;Rodriguez-Villalon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%